Pengaruh Pengetahuan Perpajakan, Sosialisasi Perpajakan Dan Kualitas Pelayanan Terhadap Kepatuhan Wajib Pajak Di Kantor Pelayanan Pajak Madya Dua Jakarta Utara - Deasy Haryanti; Dian Wahyudin (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
Taxpayer compliance remains a challenge in optimizing state revenue. This low compliance rate is influenced by various factors, including tax knowledge, tax socialization, and service quality. This study aims to analyze the influence of tax knowledge, tax socialization, and service quality on taxpayer compliance at the Madya Dua Jakarta Utara Tax Office (KPP). This study uses a quantitative approach with a population of 142 individual taxpayers and a sample of 104 respondents determined using the Slovin formula. The results show that tax knowledge has a significant influence on taxpayer compliance with a regression coefficient of 0.568, a coefficient of determination value of 0.355, or an influence of socialization on taxpayer compliance of 35.5%, and a t-value of 5.552 > t-table 1.983. Tax socialization also has a significant influence with a regression coefficient of 0.791. The coefficient value is 62.6, meaning that tax socialization influences compliance by 62.6%, and the t-value is 13.058 > t-table. Service quality has a significant influence on compliance with a regression coefficient of 0.782. The coefficient value is 0.611, indicating that the influence of service quality on compliance is 61.1%, and the calculated t-value is 12.670 > t-table. Simultaneously, the three independent variables have a very strong relationship with taxpayer compliance, with a correlation coefficient of 0.811 and a coefficient of determination of 0.658, or the influence of tax knowledge, tax socialization, and service quality is 65.8%. The resulting regression equation is Y = 22.479 + 0.242X1 + 0.265X2 + 0.555X3. The F-test yielded a calculated F value of 64.256 > table F 3.09, indicating that the regression model used is significant. Thus, tax knowledge, tax socialization, and service quality, both partially and simultaneously, significantly influence taxpayer compliance at the Madya Dua Tax Office in North Jakarta. Keywords: Tax Knowledge; Tax Socialization; Service Quality; Taxpayer Compliance